Recovery after surgery: do not forget to check iron status before - Serati M; Cetin I; Athanasiou S (Dove Medical Press, 2019)
Maurizio Serati,1 Irene Cetin,2–4 Stavros Athanasiou51Department of Obstetrics and Gynecology, University of Insubria, Varese, Italy; 2Department of Women, Mothers and Neonates, Hospital Vittore Buzzi, Milan, Italy; 3Department of Biomedical and Clinical Sciences, University of Milan, Milan, Italy; 4Italian Society of Perinatal Medicine (SIMP), Milan, Italy; 5Urogynecology Unit, 1st Department of Obstetrics and Gynecology, ‘Alexandra’ Hospital, Medical School, National and Kapodistrian University of Athens, Athens, GreeceCorrespondence: Maurizio SeratiDepartment of Obstetrics and Gynecology, University of Insubria, Piazza Biroldi 1, Varese 21100, ItalyTel +39 338 909 8353Email mauserati@hotmail.comAbstract: The perioperative period poses a risk for anemia due to the high prevalence of pre-existing anemia secondary to underlying pathologies in patients who are candidates for surgery, and as a result of the increased blood loss caused by surgery. Pre-operative anemia is an independent risk factor associated with higher risk of blood transfusion and negative surgery outcomes. Anemia and iron deficiency (ID), the main causes of pre-operative anemia, can be easily diagnosed with blood testing and are readily treated before elective surgery. However, pre-surgical screening and treatment of anemia and ID are frequently overlooked. These topics were presented and discussed at the symposium entitled “Recovery after Surgery: Don’t Forget to Check Iron Status Before”, held at the 11th Annual Meeting of the European Urogynaecological Association (EUGA) in October 2018 in Milan. The objectives of the symposium were to stress the high prevalence and the consequences of pre-operative anemia, illustrated with three clinical cases of women undergoing surgery, and to choose the best option for iron supplementation. In conclusion, it is essential to take time to diagnose and treat iron deficiency anemia (IDA) before surgery. The first-line treatment is oral iron when surgery can be delayed and when there is no intolerance to oral treatment or inefficient uptake, as in the case of iron sequestration or absorption disorders. Among iron preparations, ferrous sulfate in a polymeric complex (FSPC) was found to be one of the treatments of choice to improve hemoglobin iron stores and quality of life in IDA patients.Keywords: European Urogynaecological Association, EUGA, ferrous sulfate, iron deficiency, elective surgery, tolerability, urogynecological surgery